TELAAH MAQASHID SYARIAH DALAM KEGIATAN EKONOMI PETANI TAMBAK DI DESA PANGKAHWETAN GRESIK - Mashudi, Ahmad; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Pond business is a form of economic business activity, in which humans manage, manage and control fishery biological resources wisely to gain more profits and to improve the standard of living of a farmer. Management of natural resources should be managed optimally by means of good and correct management. The formulation of the problem in this study is what is the role of pond farmer businesses in implementing maqashid sharia on the basis of implementing Islamic philanthropy in Pangkahwetan Village, Ujungpangkah District, Gresik Regency. This study aims to determine the application of maqashid sharia, by analyzing the methods and applications carried out by pond farmers towards Islamic philanthropy. This research is a field research (field research). The method used is to use a qualitative approach through a case study approach to economic relations by collecting data through interviews, observation and documentation. The informants of this study were determined using a purposive sampling method so that only certain informants were used as informants in the study.